CULTURAL ECOLOGICAL VALUES IN ORANG-ORANG PROYEK NOVEL BY AHMAD TOHARI AS AN ENVIRONMENTAL CONSERVATION MEDIUM - Abdul Karim Wirawan (Jurusan Sastra Indonesia, 2019)
This article seeks to identify the cultural ecological values contained in the Orang-orang Proyek novels, as well as their role as environmental conservation media. The method used in this study is a qualitative method, with data analysis step (1) data classification, (2) data reduction, (3) data presentation, (4) data analysis and interpretation, and (5) drawing a conclusion. The results of this study indicate the existence of cultural ecological values in the Orang-orang Proyek novel (1) the representation of nature in the cultural perspective and (2) the harmonization of human, nature, and culture. The value of cultural ecology in this novel can be used as media to arouse readers in environmental conservation efforts.